Produktivitas Alat Gali Muat Komatsu PC2000 Dan Caterpillar 6020B Pada Kegiatan Pengupasan Overburden Di Pit OS PT Bukit Makmur Mandiri Utama Site Lati Berau Kalimantan Timur - Tyas, Yoritaning; Andy Erwin Wijaya; Hidayatullah Sidiq (ReTII, 2023)
Bukit Makmur Mandiri Utama at the Lati site set a productivity target for coal mining equipment for stripping overburden in pit OS of 660 bcm/hour for the Komatsu PC2000 unit and 698 bmc/hour for the Caterpillar 6020B. The actual productivity of the dig-loading equipment was 538 bcm/hour on the Komatsu PC2000 unit and 404 bcm/hour on the Caterpillar 6020B unit, with no productivity results yet. This is caused by factors that affect the productivity of mechanical devices. Factors affecting the failure to achieve the productivity target are the low Cycle Time of the mechanical device and the low Effective Utilization value. The aim of this research is to determine the actual productivity of the digging equipment and to optimize the productivity of mechanical equipment so that the productivity target of the loading and digging equipment can be achieved. After simulation and data analysis, improvement efforts that can be made are by applying the Top Loading, loading pattern to the dig-loading equipment so that the Cycle Time becomes 29 seconds according to the standards set by the company, as well as increasing the Effective Utilization performance value by reducing standby time. so the EU value rose to 66% for the Komatsu PC2000 unit and 68% for the Caterpillar 6020B unit. After repairs were made at the time of circulation, the productivity of the digger increased to 660 bcm/hour on the Komatsu PC2000 unit and the Caterpillar 6020B unit to 698 bcm/hour where the productivity of the digger was achieved. Meanwhile, if only the EU value is repaired, the productivity of the Excavator is 568 bcm/hour on the Komatsu PC2000 unit and the Caterpillar 6020B unit, which is 417 bcm/hour, which indicates that productivity has not been achieved.